Prayers for remembering in the Psalms - Daffern, M (2014)
The Hebrew language of remembering is complex and theologically interesting. The effective, relational, actualising aspects of zkr are particularly evident in language of prayer, especially in Psalm texts. Prayer is a remembering of God, a reminding of God, and a call to remember the pray-er herself, and such performative illocutions are addressed to both human and divine audience alike. The texts become not only present acts of remembering, but also means by which future acts of remembering are to be performed. Questions in Psalms criticism, of public or private Sitz-im-Leben, of form classification, and the ongoing debate about which critical methods to bring to Psalms scholarship, are brought together in an attempt to answer how remembering in prayer works in the Psalms. By employing hermeneutics informed by linguistics, not only the semantic field of zkr may be studied, but also pragmatic questions appropriately tackled. Thus the potential contributions of speech-act theory and discourse analysis when applied to the Psalms are indicated, alongside what comparable work has already been done by others in Psalms scholarship in these areas. Further linguistic insights which have not previously been applied to Psalms study, such as Audience Design, are then also brought to bear. Broader areas such as the theological nexus of memory, prayer, place and time, are then explored. Memory is thus seen to be an important constituent of Psalmic prayer at all levels of analysis, as a tool by which prayers are passed down and God and his people remain in relationship. Connections between remembering, didactic, and Wisdom are noted. The centrality of memory in the performance of prayer is viewed as a prototype for New Testament prayers, culminating in the Eucharist and evident for instance also in the Lord’s Prayer. Memory, in prayer texts and in their hermeneutics, both enshrines the past, and makes an ever-relevant present anticipate the future.